Extended-Spectrum β-Lactamase–Producing Escherichia coli in Neonates and Listeria monocytogenes in Young Children with Bacterial Meningitis in Japan. Issue 3 (16th December 2022) - Furuichi, Munehiro; Yaginuma, Mizuki; Shinjoh, Masayoshi; Ohnishi, Takuma; Takahashi, Takao; Iwata, Satoshi
Abstract: Nationwide surveillance of pediatric bacterial meningitis in Japan from 2019 to 2021 revealed two uncommon situations not covered by the recommended empiric treatment that were not rare in Japan, namely, extended-spectrum β-lactamase–producing-producing Escherichia coli in neonates and Listeria monocytogenes in children older than 1 month. Abstract : Nationwide surveillance of pediatric bacterial meningitis in Japan from 2019 to 2021 showed that most cases were covered by recommended empiric therapy, with two exceptions: ESBL-producing Escherichia coli in neonates and Listeria monocytogenes in young children.